Metode Tasawuf Meningkatkan Status Kesehatan Reproduksi Remaja melalui Peer Educator Siswa SMP - Aisyaroh, Noveri; Sarjuni, Sarjuni; Wahyuni, Sri (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
Adolescence is a transmission period to adulthood involving a physical, physic and social changes. Adolescents seeking for identity tend to be reckless in dealing with problem including sexuality and reproductive health problem. Unhealthy behavior can be seen from the two perspectives (environment and growth). According to Islam the healthy  social interaction should do no harms to oneself and others. Islam has a rule the adolescent social interaction. SMP Islam Nudia and SMP Kesatian 2 Semarang are our partness in PKM, both have a similar problem related to juvenile delinquency in which  the information related to reproductive health are commonly obtained from internet and  lack of understanding on the proper social interaction based on Islam. The method applied was an education on the reproductive health for the students grade 7 and 8 using  tasawuf,  physical examination of female students, the role of school health unit  (UKS)  and training for UKS personnel as peer educator. The education can improve the knowledge and awareness and behavior. The Hb evaluation showed a case of moderate and severe anemia. There was a standardized UKS and UKS as peer educators in the  schools.